The examination of marital adjustment in wives of the patients with alcohol dependence disorder - Kıvanç, Nazan; Kokurcan, Ahmet; Özgür İlhan, İnci (Journal of Dependence, 2017)
Introduction: Alcohol dependence disorder (ADD) causing gross social and occupational disabilities, is a high prevalent psychiatric disorder in population. Burnout, depression, and anxiety disorders are common in the family members, especially in spouses of the ADD patients. It was aimed to identify the relationship between marital adjustment and gender roles in wives of the patients with ADD in this study. Method: The sample of the study consists of 33 wives of the alcohol dependence disorder (according to DSM-IV-TR criteria) patients who were applied to a University Hospital Alcohol Use Disorder Clinic to stop alcohol use. Sociodemographic questionnaire, Marital Adjustment Scale (MAS), Maslach Burnout Inventory (MBI), Bem Sex Role Inventory-Short Form (BSRI), and Beck Depression Inventory (BDI) were applied to the wives of AUD patients. The results were analyzed with correlation analysis, Student’s t test and logistic regression analysis. Results: Marital adjustment scores showed a negative correlation with “emotional exhaustion”, “depersonalization”, and BDI scores (P=0.005, P=0.028, P=0.032). There was a negative correlation between depression scores and “personal accomplishment” scores (P=0.037) while depression scores were positively correlated with “emotional exhaustion” and “depersonalization” scores (P=0.034, P=0.000). Marriages longer than ten years, emotional exhaustion, and masculinity scores were found to be predictors of marital adjustment (P=0.006, P=0.004, P=0.016, respectively) according to the regression analysis. While emotional exhaustion and marriages longer than ten years was negatively correlated with marital adjustment, masculinity was associated positively with marital adjustment.